Desenvolvimento de compósitos cerâmicos refratários silico- luminosos contendo cinza da casca de arroz e wollastonita - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Aiming to develop sustainable refractory ceramic composites using rice husk ash (RHA) as a source of silica, the microstructural, physical, mechanical and thermal performance of six formulations were evaluated. The first one, taken as reference, containing 100% clay (A) and another four containing partial replacement of the aluminum oxide enriched with aluminum oxide by 10% (AS) and by microfibers of wollastonite at 5% (ASW-5), 10% (ASW-10) and 20% (ASW-20). For comparison purposes, an additional formulation containing only clay and microfiber (AW-20) were set. Regarding the materials physical properties, were measured its mass variation, linear retraction, water absorption, apparent porosity and bulk density. In mechanical analysis, compression strength and three-point bending resistance were determined. It was evaluated the thermal performance through thermal conductivity and thermalshock tests in the following temperatures: 500 ° C, 850 ° C and 1000 ° C. Rice husk ash has shown to be an excellent ceramic precursor exhibiting high amorphous silica content. Regarding the physical properties, the clay substitution per RHA and different percentages of microfiber resulted in an increase in water absorption and apparent porosity and a reduction in the linear retraction. The microfibers incorporation generated a decrease in the compressive strength and an increase in the three-point bending resistance. The thermal conductivity was inversely proportional to the porosity and the microfiber percentage. In thermal shock performance, the formulation that most strongly resisted was formulation A, and as the thermal-shock temperature gradient was increased, the composites resisted to fewer cycles. The chemical phases determined before and after the sintering process were consistent with the chemical analysis results by x-ray fluorescence. It were found typical phases from the Al-Si system, such as primary mullite, corundum, quartz and from Al-Si-CaO system, such as wollastonite, anortite, guelenite and kyanite. In addition, the formulations that presented the anortita phase were, respectively, the hardiest formulations. Key words: Refractory ceramic composites. Rice husk ash. Wollastonite. Thermo mechanical performance. Chemical transformations.
Keywords: Engenharia; Compósitos; Arroz; Engineering; Composites; Rice; CNPQ::ENGENHARIAS